Proposed TPM Implementation Process based on Organisational Readiness for Change - Susomrith, Paisith; Rermlawan, Sineenat (Advances in Social Sciences Research Journal, 2018)
Total Productive Maintenance (TPM) is the evolution of Preventative Maintenance (PM) and provides greater benefits to an organisation including an increase in productivity and manufacturing efficiency and reduced manufacturing costs. Although the benefits of TPM are well documented numerous barriers have limited the practical application of this theory. Drawing on Lewis’ (1951) change model and Weiner (2009) Organisational readiness for change construct this paper proposes an implementation process for TPM that aims to minimise barriers and motivate employees while preventing premature commencement of the implementation phase thereby averting implementation failure. To preserve the change, once TPM has been implemented the change is re-frozen.